Medulloblastomas of the Cerebellum in Children: Clinicopathologic Comparison - V. V. Morgun; О. G. Chernenko; I. A. Malovichko; S. O. Rudenko; Т. A. Malysheva; V. P. Sil'chenko; L. M. Verbova (Zaporozhye State Medical University, 2017)
Abstract Embryonal neuroepithelial tumours of the brain, grade IV are mainly observed in children and are characterized by rapid metastatic spread and frequent recurrence. The aim of the work is to compare structural features of medulloblastomas of the cerebellum in children of different age groups taking into account localization, metastatic spread and treatment outcomes. Materials and methods. The results of complete examination and surgical treatment of 289 children with medulloblastoma of the cerebellum at the Department of Pediatric Neurosurgery of Institute of neurosurgery named after A.P. Romodanov over the period of 1993-2013 were analysed. The children's age ranged from 1 month to 17 years: peak of medulloblastoma detection was registered at the age of 4-7. Results. As part of the study all the patients were divided into four age groups. Younger children rarely had brainstem lesion. In children of older age brainstem lesion, invasion into cerebral aqueduct with the development of noncommunicating hydrocephalus were registered. Total resection of medulloblastoma in younger children was performed in 40 % of cases, subtotal - in 42 %, partial - in 18 %. In children of older age total resection of medulloblastoma was carried out in 36%, subtotal - in 52 %, partial - in 12 % of cases. Histological analysis of tumours involved morphological characteristics of general histoarchitecture, correlation between parenchymal and stromal component, presence of Homer Wright pseudorosettes, collonar structures, pale insulas, true ependymal rosettes, formation of braided collonar structures, prevalence of small low-differentiated structures, number of mitoses, neoangiogenesis and angioproliferation, presence of colliquative and coagulation necroses, evidence and type of invasion, lymphocytic infiltration of tumour tissue. The following variations were defined histologically: classical - 9470/3 in 34 cases (17.9 %), desmoplastic/nodular - 9471/3 in 17 cases (8.9 %), with extensive nodularity - 9471/3 in 59 cases (31.2 %), large-cell (anaplastic) - 9474/3 in 51 cases (26.9 %), does not belong to any of the above (transitional/combined) - 9470/3 in 28 cases (15.1 %). Conclusions. It was established that survival index after total and subtotal tumour resection was not significantly different; a negative prognostic factor was only a partial removal of the tumour.